EVALUATION OF ANEMIA ACROSS THE SPECTRUM OF CHRONIC LIVER DISEASE: A DESCRIPTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic Liver Disease is associated with various hematological abnormalities, among which anemia is one of the most common complications. The etiology of anemia in chronic liver disease is multifactorial and includes nutritional deficiencies, gastrointestinal blood loss, hypersplenism, and bone marrow suppression. Identification of the type and severity of anemia is important for appropriate clinical management and prognostic assessment. Methodology: This hospital-based observational descriptive study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from December 2024 to December 2025. A total of 100 chronic liver disease patients with hemoglobin levels less than 10 g/dL were included in the study. Detailed socio-demographic, clinical, and laboratory data were collected using a structured proforma. Hematological and biochemical investigations were performed to evaluate the type, severity, and associated factors of anemia. Statistical analysis was performed using SPSS version 26.0. Results: The majority of patients were males (81%) with a mean age of 46.7 years. Alcohol-related liver disease was the most common etiology. Iron deficiency anemia was the predominant type of anemia observed, while folic acid deficiency anemia was common among alcohol-related liver disease patients. Moderate anemia was present in 63% of patients, followed by mild anemia (23%) and severe anemia (14%). Conclusion: Anemia is highly prevalent among chronic liver disease patients and is commonly associated with nutritional deficiencies and hepatic dysfunction. Early diagnosis and appropriate management may improve patient outcomes and quality of life.